Frontiers in Transplantology - Abdeldayem, Hesham; El-Kased, Ahmed F.; El-Shaarawy, Ahmed (IntechOpen, 2016)
This book is addressed to researchers, practicing physicians, and surgeons in the field of organ transplantation, as well as the medical students, residents, and fellows. The topics covered include the religious concepts in organ transplantation, embryonic organ transplantation, tolerance, normothermic graft perfusion, pharmacogenetics of immunosuppressors, viral transmission in organ transplantation, pediatric and split-liver transplantation, portopulmonary hypertension, mechanical circulatory support, ex vivo lung perfusion, and ABO-incompatible kidney transplantation.